The intermediary effect of nationalism on the relationship of religion, values, and culture with unity among pre-service teachers in Malaysia - Chew, Fong Peng; Zulnaidi, Hutkemri; Hutagalung, Fonny (Universiti Putra Malaysia, 2019)
This study aims to determine the mediating effect of nationalism on the relationship of religion, value, and culture with unity among pre-service teachers in the higher learning institutions of Malaysia. A total of 230 teachers with different racial backgrounds were recruited, among whom 133 were Malays and 97 were non-Malays. The data were analyzed using SPSS 23 and AMOS 18. Nationalism has a significant yet partial mediating effect on the relationship of religion, value, and culture with unity among pre-service teachers. The MANOVA analysis revealed a significant difference in such relationship between Malay and non-Malay students. The AMOS analysis showed that culture and religion had the highest and lowest effects on nationalism and unity, respectively. These findings imply that the Ministry of Higher Learning, universities, and lecturers in Malaysia must focus on the aspects of culture, religion, values, and nationalism to enhance the unity among pre-service teachers in the country. © Universiti Putra Malaysia Press.